Reduced inter-hemispheric auditory and memory-related network interactions in patients with schizophrenia experiencing auditory verbal hallucinations - Chen, Cheng; Huang, Huan; Qin, Xucong; Zhang, Liang; Rong, Bei; Wang, Gaohua; Wang, Huiling (Frontiers in Psychiatry, 2022)
Background Inter-hemispheric disconnection is a primary pathological finding in schizophrenia. However, given the inherent complexity of this disease and its development, it remains unclear as to whether associated inter-hemispheric changes play an important role in auditory verbal hallucination (AVH) development. As such, this study was developed to explore inter-hemispheric connectivity in the context of schizophrenia with AVH while excluding positive symptoms and other factors with the potential to confound these results. Method In total, resting-state functional magnetic resonance imaging (fMRI) was used to assess 42 patients with AVH (APG), 26 without AVH (NPG), and 82 normal control (NC) individuals. Inter-hemispheric connectivity in these subjects was then assessed through the use of voxel-mirrored homotopic connectivity (VMHC) and Pearson correlation analyses. Result Relative to HC and NPG subjects, APG individuals exhibited a decrease in VMHC in the superior temporal gyrus (STG) extending into Heschl's gyrus, the insula, and the Rolandic operculum as well as in the fusiform gyrus extending into the para-hippocampus (Corrected p < 0.005, cluster size = 52). Among APG individuals, these observed impairments of inter-hemispheric connectivity were negatively correlated with Hoffman auditory hallucination scores. Conclusion These results support the schizophrenia hemitropic disconnection hypothesis, and provide novel evidence suggesting that there may be a relationship between reductions in inter-hemispheric connectivity in auditory and memory-related networks and the pathogenesis of AVH in patients with schizophrenia following the exclusion of confounding factors from other positive symptoms.